Efektifitas Penggunaan Google Meet Dalam Pembelajaran Di Sekolah Dasar Negeri Matungkas - Josly Tintingon; Herry Sumual; Elni Jeini Usoh; Viktory Nicodemus Joufree Rotty (El-Idare, 2022)
This research was conducted with the aim of finding out how effective the use of the Google Meet application is in the learning process at SD Negeri Matungkas. Selection of learning media determines the effectiveness of learning. This study uses qualitative research with data collection techniques, namely interviews. Interviews were conducted with several teachers and parents of students. After the data was obtained, it was analyzed using Miles and Humberman's theory. The results of the study show that the use of Google Meet in learning at the Matungkas State Elementary School is not very effective. The results of the study show that learning using Google Meet is less effective. This is the ability of the teacher who is not optimal in using Google Meet and the response of students is lacking during the learning process. With such circumstances certainly also affect the activities and learning outcomes of students.